Prevalence and risk indicators of non-carious cervical lesions in male footballers - Tamea Lacerda Monteiro Medeiros; Sheila Cristina Almeida Neves Mutran; Daybelis González Espinosa; Kelson do Carmo Freitas Faial; Helder Henrique Costa Pinheiro; Roberta Souza D’Almeida Couto (BMC Oral Health, 2020)
Abstract Background Non-carious cervical lesions (NCCLs) have shown a significant incidence and prevalence and have been increasingly associated with people’s lifestyles and youths. This cross-sectional study aimed to determine the prevalence of NCCLs in footballers and to address potential risk indicators. Methods Fourty-three male semi-professional footballers with an average of 27 years old completed a questionnaire and were subjected to intraoral examination in terms of cervical tooth wear, morphological characteristics of NCCLs, tooth sensitivity, occlusal/incisal wear, and malocclusion classification. Also, laboratory assays were performed to determine salivary parameters: flow rate, pH, buffer capacity, level of Ca (calcium), Na (sodium), and K (potassium) ions, and level of cortisol. The data obtained from the questionnaire and intraoral examinations were subjected to Chi-square and Poisson regression models while the data obtained from the laboratory assays were analyzed by using analysis of variance (p <  0.05). Results The prevalence of NCCLs was 39.5%. The participants presented predominantly initial lesions with signs of mechanical stress. The daily training time was found as a significant risk indicator (p = 0.028). The multivariate analysis showed a significant difference in the variables daily training time (p = 0.023), lemon water intake while fasting (p = 0.002), toothpaste type (p = 0.004), tooth sensitivity (p = 0.006); previous orthodontic treatment (p = 0.003), and occlusion type (p = 0.008). All participants presented normal salivary parameters and levels of cortisol. Conclusion The prevalence of NCCLs among footballers was remarkable. The premolars were the most affected teeth and presented symptoms/signs of initial lesions. The daily training time was a dominant risk indicator of NCCLs development. Footballers presented adequate salivary parameters and cortisol levels.